A comparative study of the effects of different bioactive fillers in PLGA matrix composites and their suitability as bone substitute materials: A thermo-mechanical and in vitro investigation. (October 2015) - Simpson, R.L.; Nazhat, S.N.; Blaker, J.J.; Bismarck, A.; Hill, R.; Boccaccini, A.R.; Hansen, U.N.; Amis, A.A.
Abstract: Bone substitute composite materials with poly(L-lactide-co-glycolide) (PLGA) matrices and four different bioactive fillers: CaCO3, hydroxyapatite (HA), 45S5 Bioglass ® (45S5 BG), and ICIE4 bioactive glass (a lower sodium glass than 45S5 BG) were produced via melt blending, extrusion and moulding. The viscoelastic, mechanical and thermal properties, and the molecular weight of the matrix were measured. Thermogravimetric analysis evaluated the effect of filler composition on the thermal degradation of the matrix. Bioactive glasses caused premature degradation of the matrix during processing, whereas CaCO3 or HA did not. All composites, except those with 45S5 BG, had similar mechanical strength and were stiffer than PLGA alone in compression, whilst all had a lower tensile strength. Dynamic mechanical analysis demonstrated an increased storage modulus ( E′ ) in the composites (other than the 45S5 BG filled PLGA). The effect of water uptake and early degradation was investigated by short-term in vitro aging in simulated body fluid, which indicated enhanced water uptake over the neat polymer; bioactive glass had the greatest water uptake, causing matrix plasticization. These results enable a direct comparison between bioactive filler type in poly(α-hydroxyester) composites, and have implications when selecting a composite material for eventual application in bone substitution.